ANALISIS BIOMEKANIKA GERAKAN TEKNIK SERVIS PADA TENIS LAPANGAN - Andhika Yudhatama; Wegianta Anggarmana Bangun; Ainun Padilah Siregar (Riyadhoh : Jurnal Pendidikan Olahraga, 2022)
A teaching program that is very important for the physical health of students, especially through directing them to carry out sports activities physically and mentally. It aims to provide direct contribution and experience when playing various sports that are selected according to the movement skills and lifestyle that are formed. This study used a descriptive qualitative method by analyzing serves in tennis through two aspects, namely biomechanics and kinesiology. The stages include data collection, analysis, summary, and drawing conclusions. This article was compiled by gathering online resources relevant to the topic. The conclusion of this article is the importance of paying attention to the position of the feet and palms so that when giving a push it can reduce loading and minimize the risk of injury. Also, it's necessary to roll your back and torso back and forth to hit the ball with full force but not sluggish.